Characterizing the controls on surface alkalinity in Nootka Sound, British Columbia - Miller, Una (My University, 2015)
[author abstract] Understanding the processes that alter alkalinity in estuarine systems is essential to understanding distributions of surface ocean alkalinity and by extension, atmospheric CO2 levels, as a whole. Biological activity and mixing of distinct riverine sources can alter alkalinity before it reaches the open ocean, where it plays a significant role in the capacity of water to buffer against pH change, an important concept especially in the context of climate change. This study characterize surface water alkalinity in the month of December in Nootka Sound, one of several large fjord system on the west coast of Vancouver Island, British Columbia. Measurements of alkalinity, dissolved inorganic carbon (DIC), salinity, and nutrients are used to constrain the major processes controlling it. Results show that alkalinity is largely conservative in both of the inlets studied, with no significant biological controls.
Senior thesis written for Oceanography 445
Keywords: Water chemistry; Carbon cycle (biogeochemistry); Oceanography-Observations-Nootka Sound (British Columbia)